Cidades digitais : uma metodologia para implantação - Almeida, Luiz Eduardo Fontes Mello de (2010)
n this dissertation, it held the concept of a Digital City, described the traditional approach to its construction, its objectives, technologies, applications and challenges. We also present examples of Digital Cities in Brazil and worldwide. The cost and effort of deploying Digital Cities are justified by describing the benefits brought by broadband and digital inclusion, with data from Brazil and the world. It presents a proposed methodology to assist in the implementation of a digital city discussing technical and business models to ensure the operation of services and applications as well as the sustainability of any project. To validate the methodology, presents a real project where, from a diagnosis of telecommunications of the municipal government of a city, it was discovered that it was possible the deployment of a Digital City with only the resources available and part of the savings generated by decrease the cost of telephony in the new environment.